NATIVE OR NON-NATIVE TEACHERS: A STUDY ON TERTIARY TEACHERS BELIEFS IN INDONESIA - Nugrahenny T Zacharias (Soegijapranata Catholic University, 2006)
ELT professionals and scholars have voiced differing opinions on issues related to nativeness. Given the lack of empirical studies on this topic, the present study aims to document perceptions of non-native teachers on the issues of nativeness. The participants of the study were drawn from one hundred English teachers taught at tertiary level in Indonesia. The study found that the teachers beliefs about the issue of nativeness varied considerably depending on the language skill concerned. However, most respondents agreed that nativeness should not be the determining factor of what constitute a good teacher of English, as educational background and teaching skills should be taken into account. This study learns that the role of non-native English-speaking teachers needs to be further explored and socialized particularly in Indonesia where such issues are rarely addressed.